2019
DOI: 10.3390/molecules24071416
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Fractionation and Acetone Precipitation for Crude Saponins from Eurycoma longifolia Extract

Abstract: Eurycoma longifolia is a popular folk medicine in South East Asia. This study was focused on saccharide-containing compounds including saponins, mainly because of their medical potentials. Different organic solvents such as ethyl acetate, butanol, and chloroform were used to fractionate the phytochemical groups, which were consequently precipitated in cold acetone. Solvent fractionation was found to increase the total saponin content based on colorimetric assay using vanillin and sulfuric acid. Ethyl acetate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…It is well known that ethanol (relative polarity 0.654) can dissolve polar compounds, such as sugar, amino acid, glycoside compounds, phenolic compounds with medium polarity, aglycon flavonoids, anthocyanins, terpenoids, flavones, and polyphenols [ 28 ], indicating that EtOH extract is a complex mixture of organic compounds. Based on the liquid–liquid extraction technique, highly polar substances, such as organic acids, polysaccharides, free sugars, and proteins stay in the aqueous phase, whereas other relatively less polar compounds, such as terpenoids and polyphenols, are more soluble in organic solvents [ 29 , 30 ]. To enrich the active compounds in S .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that ethanol (relative polarity 0.654) can dissolve polar compounds, such as sugar, amino acid, glycoside compounds, phenolic compounds with medium polarity, aglycon flavonoids, anthocyanins, terpenoids, flavones, and polyphenols [ 28 ], indicating that EtOH extract is a complex mixture of organic compounds. Based on the liquid–liquid extraction technique, highly polar substances, such as organic acids, polysaccharides, free sugars, and proteins stay in the aqueous phase, whereas other relatively less polar compounds, such as terpenoids and polyphenols, are more soluble in organic solvents [ 29 , 30 ]. To enrich the active compounds in S .…”
Section: Resultsmentioning
confidence: 99%
“…This is an important step in bio-guided assays of new phytochemical ingredients [ 32 ]. Chua et al [ 33 ] reported that highly polar substances, such as organic acids, polysaccharides, and proteins, might remain in the aqueous phase, while the other less polar compounds, including terpenoids, could be segregated into the organic phase. More specifically, the ethyl acetate fraction had the highest levels of saponins, which include ginsenosides.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, polyphenols, high molecular weight polysaccharides and glycoprotein were also founded in root of E. longifolia (Tsai et al, 2020). Polar to semipolar saponins have been founded in E. longifolia roots (Chua et al, 2019).…”
Section: Phytochemical Compoundsmentioning
confidence: 97%